ASSESSMENT OF TWO DISCRETIZATION SCHEMES FOR HEAT CONDUCTION AND PHASE CHANGE MODELING - Ramis, Jacqueline Elhage; Queiroz, Paulo Ivo Braga de; Lucena Neto, Eliseu; Azevedo, Alex Guimarães de; Hemsi, Paulo Scarano (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Heat conduction and phase change problems are discretized in space by means of finite elements based on Ritz and collocation methods, while the time discretization stems from a fully implicit scheme. These formulations have their performances assessed by comparing the numerical results with the exact solutions of problems in semi-infinite media, either in pure diffusion without phase change - one-phase Stefan problem - or in conduction with phase change - two-phase Stefan problem. Convergence analyses reveal that the Ritz method is better suited to one-phase Stefan problem, while the two-phase Stefan problem is better treated by the collocation method.